Examining the Heterotopic Dimension in Dystopian Novels: Fahrenheit 451 as a Case Study - Takhi, Mhammed; Djoudi, Nouha Souad; Aribi,Brahim (University of Ammar Theledji -Laghouat, 2021)
Michel Foucault’s concept of heterotopia, ever since it was introduced, has garnered the interest of various domains, such as architecture, sociology and literature. The wide adaptation and appropriation of this concept is a result of its ambiguous definition. Heterotopia seems as though it is inherently contradictory, for it is described as both an impossible space only represented in language; and a real space of otherness that contests other spaces surrounding it. On this account, this paper makes use of the concept and employs it by identifying with its literary origins, and attributing it with metaphorical and literary spaces rather than physical places exclusively. To this end, this work considers Foucault’s account of heterotopia and attempts to identify its principles with elements from Ray Bradbury’s Fahrenheit 451 as the very concept of heterotopias entails. Even more importantly, relating the novel to the principles of heterotopias brings the heterotopic dimension existing in the novel even forward, which subsequently allows it for better understanding